Non-performing loans (NPLs), liquidity creation, and moral hazard: Case of Chinese banks - Muhammad Umar; Gang Sun (China Finance and Economic Review, 2016)
Background: This study analyzes the impact of non-performing loans (NPLs) on bank liquidity creation to investigate the existence of moral hazard problem in Chinese banks. Methods: It uses data from 197 listed and unlisted Chinese banks, spanning the period 2005 to 2014. Generalized method of moments (GMM) estimation, fixed and random effect model, and pool data techniques have been used for analysis. Results: Total liquidity creation by Chinese banks is declining, and NPLs ratio has started to increase following a continuous decline between 2005 and 2012. We find that liquidity creation by Chinese banks does not depend on NPLs ratio. We repeated the analysis for small and large banks and the results of these subsamples reinforced our findings for the aggregate sample. Conclusions: We did not find the evidence of moral hazard problem in Chinese banks.
Keywords: G21; G28; 330; Bank; Liquidity creation; Non-performing loans; Moral hazard; China